THE KONIMEX DISTRICT AND THE KARAKALPAKS IN THE BUKHARA EMIRATE, A VASSAL OF THE RUSSIAN EMPIRE (LATE 19TH - EARLY 20TH CENTURIES) - Nurkhan Jenisovich Mamatsharifov, (Journal of Applied Science and Social Science, 2026)
This article comprehensively examines the historical development, governance, and political situation of the Kenimekh district within the Bukhara Emirate, which existed as a vassal state of the Russian Empire in the late 19th and early 20th centuries, as well as the life and economic lifestyle of the Karakalpaks in this region. The article also extensively examines the processes of Karakalpak migration to the territory, auxiliary livestock farming, agriculture, and crafts related to their economic activities. Changes in the ethnic composition of the population, individual lifestyle, and social relations are shown based on historical sources.